Color Symbolism in the Castilian Atlantic Bibles: Initials and Scenes from the Bible of Avila (BNM, Vit. 15-1) - Maria Rodriguez Velasco (Multidisciplinary Journal of School Education, 2020)
The Atlantic Bibles of the Umbro-Roman school are associated with the needs of the Gregorian Reform, which began at the end of the 11th century. Their first impression is one of great ornamental sobriety, in accordance with the early stages of what Garrison and Berg have labelled the “geometric style.” This was first manifested in the decoration we find concentrated in the initials heading the individual books of the Bible. In Castile, one outstanding example is the Bible of Avila, begun by the Umbro-Roman school and finished in a Castilian scriptorium. This double perspective can be observed in a similarly double palette of color: Italian and Spanish.